2020
DOI: 10.1080/13216597.2020.1817122
|View full text |Cite
|
Sign up to set email alerts
|

Destruct, direct and suppress: Sputnik narratives on the Nordic countries

Abstract: Projection of strategic narratives to gain competitive advantages is a central feature in the global competition for status and power. This article presents a comparative narrative analysis of how the Russian state sponsored news platform Sputnik narrates Denmark, Finland, Norway and Sweden 2014-2019. The objectives are to uncover what negative work strategic narratives can perform and to decipher how adverse narratives are constructed. The findings suggest that Sputnik uses a mix of standard strategies and ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 43 publications
0
28
0
3
Order By: Relevance
“…Flaherty and Roselle, 2018;Khaldarova and Pantti, 2016;Ramsay and Robertshaw, 2019) would be a cogent and productive step here. To illustrate this, let us briefly consider Wagnsson and Barzanje's (2019) analytical framework examining the geopolitical functions of Sputnik's antagonistic narration of Sweden, and expanded later to the Nordic countries (Deverell et al, 2020). The proposed framework delineates three key strategies that each fulfil a particular strategic goal for the Kremlin, including 'destruction', described as a narrative strategy that aims to undermine perceptions of a target state's 'military resolve, economic strength, and governmentality' (Deverell et al, 2020: 4).…”
Section: Generating Theoretical Modelsmentioning
confidence: 99%
“…Flaherty and Roselle, 2018;Khaldarova and Pantti, 2016;Ramsay and Robertshaw, 2019) would be a cogent and productive step here. To illustrate this, let us briefly consider Wagnsson and Barzanje's (2019) analytical framework examining the geopolitical functions of Sputnik's antagonistic narration of Sweden, and expanded later to the Nordic countries (Deverell et al, 2020). The proposed framework delineates three key strategies that each fulfil a particular strategic goal for the Kremlin, including 'destruction', described as a narrative strategy that aims to undermine perceptions of a target state's 'military resolve, economic strength, and governmentality' (Deverell et al, 2020: 4).…”
Section: Generating Theoretical Modelsmentioning
confidence: 99%
“…Narrativ teori står sentralt i faglitteratur om Russlands kommunikasjonsoffensiv mot Norden (se bl.a. Cepurı ˉtis et al, 2020;Deverell et al, 2021). Likevel har litteraturen i liten grad belyst hvordan narrativ påvirkes av nettverksteknologi.…”
Section: Narrativ I Nettverksperspektiv: Teori Metode Og Empirisk Gru...unclassified
“…De flertydige norgesfortellingene formidlet fra russiske myndigheter suppleres av en narrativ «gråsone» 22 kontrollert av dem (Abrams, 2016). Vestlig forskning på denne gråsonen har fremfor alt latt seg fascinere av RT, ut fra forestillingen om at kringkasteren kjemper i frontlinjen av Russlands informasjonskrig -som også foregår i Norden (Berzina et al, 2018;Cepurı ˉtis, 2021;Deverell et al, 2021;Wagnsson & Barzanje, 2019). Selv på denne frontlinjen er Norge svøpt i flertydighet.…”
Section: Russiske Norgesnarrativ: Ambivalens Og Flertydighetunclassified
“…Recent studies conducted on disinformation campaigns in the countries of the V4 region and beyond have used a similar framework when assessing the role of narratives communicated. Deverell et al (2020) have conducted a comparative narrative analysis on how the news platform Sputnik narrated Denmark, Finland, Norway and Sweden between 2014 and 2019, and have found that Sputnik News utilised a mix of standard strategies and tailor -made narratives to destruct Nordic countries. They have been able to identify differences among how Sputnik narrated the countries of the region, with Sweden and Denmark being portrayed more negatively than Norway and Finland.…”
Section: Disinformation and Strategic Narratives In The V4 Regionmentioning
confidence: 99%
“…Based on the examined literature -especially Deverell et al (2020), Hinck et al (2018) and Khaldarova (2016) -our first hypothesis for the analysis was that among disinformation news pieces targeted at the Visegrád countries, we would be able to identify recurring topics, and that based on these key topics it would be possible to establish prevailing narratives and meta -narratives of disinformation campaigns targeted at the V4 region. A topic would be considered recurring based on its relative frequency of mentions and its overarching presence in various or all four datasets.…”
Section: Hypothesesmentioning
confidence: 99%